Effect of dentin biomodifiers on the immediate and long-term bond strengths of a simplified etch and rinse adhesive to dentin - Payal Singh; Rajni Nagpal; Udai Pratap Singh (Korean Academy of Conservative Dentistry, 2017)
Objectives This in vitro study evaluated the effect of dentin biomodifiers on the immediate and long-term bond strengths of a simplified etch and rinse adhesive to dentin. Materials and Methods Flat coronal dentin surfaces were prepared in 120 extracted human molars. Teeth were randomly divided into 5 groups (n = 24) according to 5 different surface pre-treatments: No pre-treatment (control); 1M carbodiimide (EDC); 0.1% epigallocatechin-3-gallate (EGCG); 2% minocycline (MI); 10% sodium ascorbate (SA). After surface pre-treatment, adhesive (Adper Single Bond 2 [SB], 3M ESPE) was applied. Composite was applied into transparent plastic tubes (2.5 mm in diameter), which was placed over the bonded dentin surface. From each group, 10 samples were subjected to shear bond strength (SBS) evaluation at 24 hours (immediate) and remaining 10 samples were tested after 6 months (delayed). Additionally, 4 samples per group were subjected to scanning electron microscopic analysis for observation of resin-dentin interface. The data were statistically analysed with Shaperio‑Wilk W test, 2-way analysis of variance (ANOVA), and post hoc Tukey's test. Results At 24 hours, SBS of all surface pre-treatment groups were comparable with the control group, with significant differences found between EDC and SA groups only (p = 0.009). After 6 months storage, EDC, EGCG, and MI pre-treatments preserved the resin-dentin bond strength with no significant fall. Conclusions Dentin pre-treatment with all the dentin biomodifiers except SA resulted in significant preservation of resin-dentin bond over 6 months storage period, without negatively affecting the immediate bond strength of the etch and rinse adhesive tested.